Enseigner et apprendre les unités parémiologiques d’une langue étrangère: du XIX e siècle à nos jours - María Inmaculada Rius Dalmau (Çédille: Revista de Estudios Franceses, 2014)
Our goal here is the study of certain textbooks for the teaching of French as a foreign language that were published in Spain throughout the nineteenth century and which contain a section dedicated to sayings, idioms and proverbs. We question the role of these tools in terms of student motivation in the acquisition of the new language and their effectiveness from a teaching perspective. Folk psychology has been remarkably influential in teaching in general and particularly in terms of lan-guages. While it is true that in the past the universe of beliefs played its role, among learners of today multiculturalism and diversity also create a new language with complex and shifting identities. As a result, cultural and language learning is based on a dependence that enables learners to come to terms with multiple identities and to take advantage of the results achieved in the past